ANÁLISE NUMÉRICA DE VIGAS MISTAS BIAPOIADAS DE AÇO E CONCRETO EM SITUAÇÃO DE INCÊNDIO VITÓRIA - Nunes, Carlos Lindemberg Emerick (2022)
The knowledge about the behavior of structures in a fire situation is essential in buildings where the preservation of structural safety and the time of vacancy are factors of great relevance. Composite systems of steel and concrete beam present several advantages in relation to the solution that uses only steel structures, among them the best structural behavior under fire conditions. The evaluation of the resistant capacity of structures in fire situation by tests in full scale is expensive, high complexity and requires a specific test structure. The alternative to these limitations is the development of computational numerical models capable of simulating the real structure in order to evaluate its behavior. This research focuses on development of three-dimensional numerical models of composite steel and concrete beams, simply supported, in a fire situation, to perform thermal and thermostructural analyzes using finite element method. Several models of composite beams are analyzed, changing the following parameters: steel beam, span length, load level, slab thickness, concrete and steel strength and reinforcement bars ratio. The numerical models, validated by experimental results of other authors, were developed using finite element method on software ANSYS and the language APDL. Finally, the thermal and thermostructural results obtained through the numerical models are compared with the values calculated by the analytical methods proposed by national and international standards.